THE IMPACT OF TELEMEDICINE PLATFORMS ON HEALTHCARE IN RURAL AREAS - Maxsudov Valijon Gafurjonovich, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation (Abstract): Telemedicine platforms have emerged as a transformative solution in improving healthcare delivery, particularly in rural areas where access to medical services is often limited. This study explores the impact of telemedicine on healthcare accessibility, quality, and efficiency in rural communities. It highlights how digital health technologies enable remote consultations, diagnosis, monitoring, and treatment, thereby reducing geographical barriers and healthcare disparities. The paper also examines challenges such as digital literacy, internet connectivity, data security, and infrastructure limitations that affect the implementation of telemedicine systems. Findings suggest that telemedicine significantly enhances patient outcomes, reduces travel costs and waiting times, and supports healthcare professionals in delivering timely interventions. However, sustainable integration requires policy support, technological investment, and training programs for both patients and healthcare providers. Overall, telemedicine represents a promising approach to strengthening rural healthcare systems and improving equity in healthcare access.